THE RELATIONSHIP BETWEEN ANXIETY LEVELS AND INCREASED BLOOD PRESSURE IN PREOPERATIVE PATIENTS WHO WILL UNDERGO GENERAL ANESTHESIA AT BEKASI REGENCY HOSPITAL - ratno; Zerin Mercillia Adisti; Suanda Saputra (Keperawatan Anestesiologi Program Sarjana Terapan, 2025)
Background: Anxiety is a common psychological response in patients before surgery, especially before receiving general anesthesia. Excessive anxiety can affect the patient's physiological condition, especially resulting in high blood pressure. Objective: To determine the relationship between anxiety levels and high blood pressure in preoperative patients scheduled to undergo general anesthesia. Methods: This study involved 36 respondents and used a cross-sectional design with purposive sampling. The Amsterdam Preoperative Anxiety and Information Scale (APAIS) questionnaire was used as a measuring tool, and a Spearman Rank test was conducted to evaluate the results. Results: Based on these findings, anxiety and systolic (P-value 0.002) and diastolic (P-value 0.003) blood pressure were significantly correlated. The majority of respondents reported higher diastolic (58.3%) and systolic (69.4%) blood pressure. Background: : Anxiety is a common psychological response in patients before surgery, especially before receiving general anesthesia. Excessive anxiety can affect the patient's physiological condition, especially resulting in high blood pressure. Methods: This paper involved 36 respondents and used a cross-sectional design with purposive sampling. The Amsterdam Preoperative Anxiety and Information Scale (APAIS) questionnaire was used as a measuring tool, and the Spearman Rank test was conducted to evaluate the results. Results: Based on these findings, anxiety and systolic (P-value 0.002) and diastolic (P-value 0.003) blood pressure were significantly correlated. The majority of respondents reported higher diastolic (58.3%) and systolic (69.4%) blood pressure. Conclusion: that high blood pressure and anxiety levels have a relationship or association The findings of the authors show that among preoperative patients who received general anesthesia, anxiety levels and high blood pressure were significantly correlated. For the procedure to be successful, the patient's hemodynamic status must remain stable, which requires effective preoperative anxiety management